Analysis of the Successful Implementation of SAP Business One in PT. P.R. Indonesia - Riszkey Leonardo; Togar Alam Napitupulu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Along with the development of information technology, more companies will need to apply information technology to their operations, especially for data processing. One of the applications of information technology is through Enterprise Resource Planning (ERP) systems such as SAP Business One. The SAP Business One system is an affordable ERP for SMEs that can be integrated into every business process and tends to be easy to use. PT. P.R. Indonesia has been implementing the SAP Business One system for 2 years but they still faced some obstacles such as bugs, error messages that cannot be understood by the user, reports generated by the system that require customization, and recommendation information that does not address the user's wants. The obstacles experienced by PT. P.R. Indonesia has prompted an analysis regarding the success of ERP implementation at PT. P.R. Indonesia. To measure and determine the success of the implementation of an information system, the determinants of successful implementation need to be analyzed. Thus, this study used the Structural Equation Modeling (SEM) method to analyze data. The SmartPLS software version 3.3.9 was used to process the data. Based on the calculations, the factors that contribute the most are implementation with the Accelerated Implementation Program (AIP) method with a value of 0.734, the Business Process Reengineering (BPR) factor with a value of 0.326, and the Vendor Support (DV) factor of 0. 354.